Prevención del dengue y estilos de vida saludables en la parroquia Santa Ana, del Cantón Santa Ana-provincia Manabí, en el período noviembre del 2013 a marzo del - Cedeño Cevallos, Shyrley Cecilia (2014)
In the parish of Santa Ana, the city of the same name , Manabi , Ecuador , a research project entitled "Prevention of dengue and healthy lifestyles in the parish of Santa Ana, Santa Ana Canton - Manabi province , in the January developed to June 2013. " The results were aimed at identifying the presence of dengue and healthy lifestyles , diagnose healthy lifestyles and incidence of dengue in the families of the parish of Santa Ana Canton Santa Ana, substantiate the theories related to the incidence dengue and healthy lifestyles and design a style guide to healthy living dengue prevention . In conclusion states that the observation of 320 households of the inhabitants of the parish of Santa Ana was evident that although there are styles of unhealthy lives , the population maintains an acceptable knowledge about dengue prevention From the results obtained in observing the lifestyles related to preventing unfair terms are kept in compliance levels high , medium, low and none , showing that an average of 39.9 % perform no action , 28 , 7% have a higher level of compliance , 22.1 % medium, and low is 22.1 %, which shows that in most households there are no healthy lifestyles to prevent dengue. Surveys to measure the actions and the level of knowledge of the inhabitants of the community about the knowledge of the transmitting agent of dengue , 75.3 % believe that is transmitted by mosquitoes and 24.75 because of the rains, be considered in these responses that a significant number of people attribute the onset of winter the onset of disease in the total survey there an acceptable level of knowledge of the population, although not applied in their lifestyles .